2013
DOI: 10.1167/iovs.12-10952
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Scleral Biomechanical Behavior Related to Susceptibility for Retinal Ganglion Cell Loss in Experimental Mouse Glaucoma

Abstract: Longer eyes, greater scleral strain in some directions at baseline, and generalized scleral thinning after glaucoma were characteristic of CD1 mice that have greater tendency to retinal ganglion cell damage than B6 mice. Increased scleral stiffness after glaucoma exposure in mice mimics findings in monkey and human glaucoma eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 70 publications
(89 reference statements)
13
88
0
Order By: Relevance
“…18,42 A growing body of research has shown that the sclera becomes stiffer in glaucoma. 7,43,44 These latter findings would support a link between myofibroblast-mediated detrimental sclera remodeling and mechanical damage to the ONH.…”
Section: Discussionmentioning
confidence: 75%
“…18,42 A growing body of research has shown that the sclera becomes stiffer in glaucoma. 7,43,44 These latter findings would support a link between myofibroblast-mediated detrimental sclera remodeling and mechanical damage to the ONH.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, the two measures of scleral thickness change in opposite directions in glaucoma mice. Fresh PPS is significantly thinner after glaucoma, while the fixed sclera in epoxy sections is thicker Nguyen et al, 2013). This would suggest that nonfibrillar (water soluble) components of the scleral matrix decrease or at least lose their capacity to bind water (thinner fresh sclera), while there is a small but significant increase in fibrous components, chiefly collagen (thicker fixed sclera).…”
Section: Scleral and Onh Changes In Mouse Glaucomamentioning
confidence: 99%
“…8 Scleral thickness is greatest at the peripapillary zone, followed by the limbus, and is thinnest in midsclera. [9][10][11][12] The scleral collagen fibril diameter is larger 13 and varies more than in the cornea 14 or the lamina cribrosa of the ONH. 15 Scleral collagen fibrils, mostly type 1, are arranged in stacked and interwoven lamellae in which most fibrils course in parallel, with successive lamellae alternating in orientation.…”
mentioning
confidence: 99%
“…16 Aca23 mice (mice of B6 background that are homozygous for mutation in collagen 8a2) are significantly protected against injury from experimental glaucoma, 30,31 while CD1 mice are considerably more susceptible to damage than B6 mice 32 and differ in important features of scleral anatomy and response. 9,33 Experimental glaucoma in mice increases axial length and width by 6% to 10%, with thinning of the peripapillary sclera and increased scleral stiffness in mechanical inflation testing. Types of mice that are more resistant to glaucoma injury have stiffer sclera in mechanical testing at baseline, and with chronic IOP increase, they undergo less midscleral thinning and resist axial elongation better.…”
mentioning
confidence: 99%
See 1 more Smart Citation